A systematic review of the use of motivational interviewing in the management of hypertension - Abdulloh, Ahmad Abdul Ghofar; Yusuf, Ah.; Qur’aniati, Nuzul (Media Keperawatan Indonesia, 2023)
Non-adherence in hypertensive patients is a serious challenge faced by health workers. The motivational interviewing (MI) is a patient-centered intervention and has been shown to change a person's compliance. The aim of this review is to investigate the impact of MI on adherence in hypertensive patients. This review was conducted on four databases, PubMed, Cinahl, Web of Science (WOS), and Scopus. Only randomized controlled trial (RCT) articles were used in this review, the quality assessment of the articles used the JBI critical appraisal tools, the selection and extraction of articles referred to the PRISMA guidelines. There were 5 articles that met the inclusion criteria. MI is applied with 2 methods, conventional and non-conventional. 2 articles showed an increase in medication adherence, 1 article showed adherence to dietary and physical activity recommendations, 1 article showed a change in smoking consumption patterns, and 4 articles showed a decrease in blood pressure in post-intervention hypertensive patients. MI can be an effective option in terms of improving hypertension adherence in the future. Although the evidence is currently validated, more research is needed to explore the evidence for the effectiveness of the combined MI method.